Análisis del cronotopo bajtineano en “El jardín de los senderos que se bifurcan” de Jorge Luis Borges - Castillo Contento, Javier Alexander (2024)
The general objective of this research was to analyze the discursive strategies of the chronotope in the story "El jardín de los senderos que se bifurcan" (The Garden of Forking Paths) by Jorge Luis Borges, one of the most emblematic works of magical realism, which it represented a starting point. For the theoretical development of time and space through literature towards other branches of science. The methodology used responds to a qualitative approach. Consequently, it is a descriptive and documentary research, whose corpus of analysis was constituted by the literary work in question; For the analysis and interpretation of the information, the analytical-synthetic, historical-logical, hermeneutic, and critical-evaluative methods were used; in addition to documentary and content analysis techniques. The results of the investigative work specify that the symbology of the chronotope in Borges's story is established from semantic fields related to time/space, strategy, chance, chess, creativity, and death. While there is this inseparable correlation between space and time, so that it is not possible to understand one without the other, in addition to its exploration through labyrinths, enigmas and philosophy, where the literary chronotope enriches the understanding of the story through a different vision.